Clinical Efficacy of Posterior Percutaneous Endoscopic Unilateral Laminotomy with Bilateral Decompression for Symptomatic Cervical Spondylotic Myelopathy - Xiao‐bing Zhao; Ya‐jie Ma; Hai‐jun Ma; Xin‐yu Zhang; Hong‐gang Zhou (Orthopaedic Surgery, 2022)
Objective To compare the clinical efficacy of posterior percutaneous endoscopic unilateral laminotomy (PPEUL) and anterior cervical decompression and fusion (ACDF) in the treatment of single‐segment spondylotic myelopathy (CSM). Methods This is a retrospective research, from January 2017 to December 2019, 30 cases were included in the PPEUL group and 32 cases were included in the ACDF group. The operative duration, blood loss, length of stay, complications, Japanese Orthopaedic Association (JOA) score, visual analogue scale (VAS) score, MacNab classification and imaging data were collected preoperatively, postoperative 1‐week, final follow‐up and statistically analyzed. Results The surgery was completed successfully on all patients, and there were no serious complications, such as nerve or spinal cord injury or infection. In the PPEUL and ACDF groups, the operative duration were 56.63 ± 1.40 and 65.21 ± 2.45 min, the intraoperative blood loss were 51.69 ± 3.23 and 50.51 ± 5.48 mL, and the hospitalization duration was 5.75 ± 1.43 and 6.38 ± 2.16 days. The follow‐up period in the PPEUL and ACDF groups was 24.96 ± 1.12 months and 25.65 ± 1.45 months, respectively. There was no significant difference in intraoperative blood loss between the two groups, but the hospitalization and operative durations in the PPEUL group were significantly shorter than those in the ACDF group (P < 0.05). The VAS scores at postoperative 1 week and final follow‐up were significantly improved compared with those before surgery. The JOA scores at postoperative 1 week and final follow‐up were significantly improved compared with those before surgery, but there was no significant difference between the two groups at the last follow‐up. The intervertebral disc height of the adjacent segment at the last follow‐up was significantly lower in the ACDF group than in the PPEUL group (P < 0.05), but there was no significant difference between the two groups in the intervertebral disc height of the surgical segment (P > 0.05). The rate of excellent and good results was 90.0% and 87.5%, respectively. Postoperative cervical CT and MRI showed that the spinal canal was fully decompressed and spinal cord compression was relieved. Conclusion PPEUL has the advantages of reduced trauma, rapid recovery and remarkable curative efficacy, so it is a new choice for the treatment of CSM.